A Food Safety Belief Model for Latino(A) Employees in Foodservice. (August 2013) - Cho, Seonghee; Hertzman, Jean; Erdem, Mehmet; Garriott, Patton O.
Reducing the risk and occurrence of foodborne illness is a priority for the foodservice industry. Despite the large presence of Latino(a)s in the foodservice workforce, there is little research on attitudes toward food safety and related behavior among this group. This study employed the health belief model to investigate Latino(a) foodservice employees' attitudes toward food safety and the antecedents of food safety behavior. Results showed that food safety knowledge did not affect self-reported food safety behavior but did significantly predict perceived susceptibility, severity, and barriers. The analysis also indicated that perceived benefits have a direct impact on food safety behavior.